A caminho da periferia: a descentralização católica em Montes Claros -1980 1990 - Barbosa, Denílson Meireles (2010)
This study examines the role of the Catholic Church in Montes Claros in the late twentieth century, a period marked by strong urbanization process, especially from the incentive fiscal through Sudene. It is understood that the possibility of living in the city and getting a job is a good attraction to those living in rural areas. For this stimulus, many moving to the city, almost always, to live in precarious conditions in the periphery, because it does not provide the basic conditions of social welfare. Those who come to inhabit this new space bring their experiences, especially with the practice of religion, that will be experienced in the context of urbanization. They seek a reorganization of everyday life through the bonds of affection with their neighbors in the community. Religion appears to be an important channel to lead the new residents of the city, visit the origin, for there on the periphery, retranslate codes of life, and reinvent their identity from their cultural roots. In this context, there is the displacement of the Catholic Church to the periphery. Movement hard for this religious institution, which will have to learn to speak the language of the common people, to understand the rituals of everyday life, and symbols of popular religion backlands experienced there. Our purpose was to try to understand as it was the decentralization of the Church in urban areas, the center to the periphery, therefore, this appears to involve a restructuring of the Church that made possible a new methodology to work in the city. We selected as time line, the last two decades of the past, understand that this period is happening most significant changes to the Catholic Church in Montes Claros